MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN SISTEM PERSAMAAN LINEAR TIGA VARIABEL MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING KELAS X MIPA 1 SMA NEGERI 5 DENPASAR - Wayan Kariasa (LP3M Universitas PGRI Mahadewa Indonesia, 2020)
The purpose of this research is to improve the motivation and learning outcomes of class X MIPA 1 SMA Negeri 5 on the material of three-variable linear equation systems. This type of research is classroom action research (PTK). This research was conducted at SMA Negeri 5 Denpasar. Subjects in the research of class X MIPA 1 students of SMA Negeri 5 Denpasar in the even semester of the 2019/2020 academic year, and the object of this study was the understanding of the material of the three-variable linear equation system and student learning motivation towards the problem-based learning model. In this study, several cycles were used through four stages of the activity process which include (1) planning, (2) action, (3) observation, and (4) evaluation and reflection. The results showed that the application of the problem-based learning model could improve the students 'ability to answer questions in the three-variable linear equation system and there was a positive student learning motivation towards the application of the problem-based learning model to improve the students' ability to answer questions about the three-variable linear equation system.